Difficult atheism : post-theological thinking in Alain Badiou, Jean-Luc Nancy and Quentin Meillassoux /: post-theological thinking in Alain Badiou, Jean-Luc Nancy and Quentin Meillassoux. ([2013]) - Watkin, Christopher
No abstract available